Misconception Profile of Newton’s Law Concept Using Certainty of Response Index (CRI) - Mushthofa, Zayyinul; Rusilowati, Ani; Sulhadi, Sulhadi; Marwoto, Putut; Mindyarto, Budi Naini (Universitas Negeri Semarang, 2020)
Misconception is an understanding that is believed to be correct but not according to the understanding of the experts. Misconceptions can occur because students build their knowledge gained from daily activities. This study aims to identify misconceptions about Newton's law concept and the causes of the misconceptions. The research type is descriptive quantitative. A total of 30 students of SMA Multazam IBS Semarang were given a true-false objective test and drew a style diagram accompanied by a certainty of response index (CRI). The cause of the misconception was obtained by interviewing 4 students. The results obtained were as many as 20.99% of students experienced misconceptions, 9.99% of students understood the concept, and 69.02% did not understand the concept of Newton's law concept. The most common misconception is that students think that heavier objects will fall faster than lighter objects. The cause of students experiencing misconceptions is the understanding they build themselves; students' carelessness in choosing answers; low reasoning ability; and forget the material that has been delivered.